An evaluation of Neisseria gonorrhoeae antimicrobial susceptibility testing in the UK. Issue 11 (30th July 2014) - Jain, Anu; Cole, Michelle J; Planche, Tim; Ison, Catherine A
Abstract : The only method currently available to perform Neisseria gonorrhoeae antimicrobial susceptibility testing (Ng-AST) requires a viable organism obtained by culture. Reports of in vitro resistance to extended-spectrum cephalosporins, the treatment of choice for gonorrhoea, coupled with increasing gonorrhoea diagnoses is worrying. The aim of this study was to identify various methodologies employed by the UK microbiology laboratories to perform Ng-AST. Of the 118 laboratories that responded, 114 offered Ng-AST; the majority (82.5%, 94/114) of the laboratories used British Society for Antimicrobial Chemotherapy methodology for Ng-AST. The other main findings were infrequent use of quality control procedures and inconsistent susceptibility testing of the antibiotics used routinely for treatment.